Public Parks Tourism in Jordan: Patterns, Characteristics, and Visitors’ Behavior - Alzboun, Nidal; Khawaldah, Hamzah; Albahrat, Faisal (Dirasat: Human and Social Sciences, 2020)
The study aims at examining excursion patterns and behavior of public parks visitors in Jordan. It also aims to identify the motivations of visitors to visit public parks in Jordan to reveal their attitudes towards harmful practices on the parks environment in the study area, and to find out the relationship between the social and economic characteristics of the study sample and their behaviors. In addition, it seeked to providing possible suggestions to address problems in these parks from visitors’ perspective. To achieve these objectives, the analytical statistical approach was used to analyze obtained data which was collected from the questionnaire that was distributed to a convenience sample of (556) visitors. Of them, 540 were suitable for analysis. The analysis was, however, performed on (540) proper questionnaires and the appropriate statistical methods were used to analyse the data including frequencies, One-way ANOVA, and (T) test. The study concluded that there was a variance in visitor’s characteristics in public parks in Jordan were youth age group and males represented the highest percentage among study sample. It also revealed that family tourism is the dominant pattern in public parks. Regarding tourism services, respondents indicated that there is a lack of infrastructure especially toilets, and barbeque places which negatively affected visitors’ satisfaction. In addition, negative behaviors were noticed by the study sample including smoking and leaving litters inside public parks. Thus, the study recommended conducting awareness campaigns to the local community to preserve parks’ environment from these negative behaviors. In addition, the study recommended to impose fines by environmental police, and to legislate needed laws to prevent these behaviors in public parks in Jordan.